Health decline in prison and the effects of sporting activity: results of the Hessian prison sports study - Mutz, Michael; Müller, Johannes; Justus Liebig University Giessen (My University, 2023)
Background: Previous studies about health in prisons conclude that incarceration has detrimental consequences for physical and mental health. It is associated with weight gain, decreased fitness, increased cardiovascular risks, and increased risks for mental illnesses, like depression and anxiety. This article examines the relationships between sports activity and health developments among prisoners. We analyze data from the Hessian Prison Sports Study, conducted in 12 prisons of the federal state of Hesse, Germany. Results: Based on quantitative survey data of 568 prisoners in regular custody, our empirical findings show that inmates perceive substantial health declines since incarceration. They report substantial decreases in general health (d=-0.52) and life satisfaction (d=-0.84) as well as an increased number of health problems (d = 0.71). However, sport has a potential to buffer this decline of health. Prisoners engaged in sports report a less negative development of their health compared to inactive prisoners. The greater the amount of time spent with sports activities, the better are the health trajectories found. Conclusion: Findings add to the public health and prison sport literature by demonstrating health benefits of sporting activities in a vulnerable population group that almost inevitably is exposed to manifold strains and burdens.
Keywords: ddc:796